2021
DOI: 10.1111/ijcp.14595
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effectiveness of intelligent volume‐assured pressure support (iVAPS) vs bi‐level positive airway pressure spontaneous/timed (BPAP S/T) for hypercapnic respiratory failure in chronic obstructive pulmonary disease

Abstract: Background and aim: Intelligent volume-assured pressure support (iVAPS) is a relatively new hybrid mode of non-invasive ventilation (NIV). There is still limited evidence for iVAPS. The aim of this study was to compare the effectiveness of iVAPS to that of bi-level positive airway pressure spontaneous/timed (BPAP S/T) in patients with acute hypercapnic respiratory failure or acute-on-chronic hypercapnic respiratory failure caused by acute exacerbation of chronic obstructive pulmonary disease (AECOPD) in the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Besides, we found better improved BG function and vital signs in groups A and C after treatment, further demonstrating the excellent application effect of BIPAP. Previous studies have suggested that BIPAP therapy can warm and humidify the inhaled gas through the upper respiratory tract, meet the needs of mask mechanical ventilation, shorten the hospitalization time of RF patients, and reduce the rate of tracheal intubation; in SPI, it can also effectively remove a large amount of inflammatory secretions in the airway, reduce airway obstruction, and improve lung ventilation and ventilation function [ 30 , 31 ]. Therefore, under BIPAP, not only the high resistance in the airway can be overcome but also the workload of the respiratory muscles and the oxygen consumption can be reduced, so as to avoid the overwork of the respiratory muscles, improve the compliance of the lungs, and adjust the oxygen partial pressure, ultimately lowering the possibility of damage to the body and other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we found better improved BG function and vital signs in groups A and C after treatment, further demonstrating the excellent application effect of BIPAP. Previous studies have suggested that BIPAP therapy can warm and humidify the inhaled gas through the upper respiratory tract, meet the needs of mask mechanical ventilation, shorten the hospitalization time of RF patients, and reduce the rate of tracheal intubation; in SPI, it can also effectively remove a large amount of inflammatory secretions in the airway, reduce airway obstruction, and improve lung ventilation and ventilation function [ 30 , 31 ]. Therefore, under BIPAP, not only the high resistance in the airway can be overcome but also the workload of the respiratory muscles and the oxygen consumption can be reduced, so as to avoid the overwork of the respiratory muscles, improve the compliance of the lungs, and adjust the oxygen partial pressure, ultimately lowering the possibility of damage to the body and other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are ASV, iVAPS and AVAPS (see Table 5). Studies using these algorithms are promising and demonstrate evidence of benefit [35–37], but are yet to be further evaluated and implemented. Other modes focus on improving synchrony and providing proportional support (NAVA and PAV).…”
Section: How To Provide Noninvasive Ventilation In Acute Exacerbation...mentioning
confidence: 99%